Metabolic pathway for propionate utilization by phosphorus-accumulating organisms in activated sludge: 13C labeling and in vivo nuclear magnetic resonance - Lemos, Paulo C. (2019)
In vivo 13C and 31P nuclear magnetic resonance techniques were used to study propionate metabolism by activated sludge in enhanced biological phosphorus removal systems. The fate of label supplied in [3-13C] propionate was monitored in living cells subjected to anaerobic/aerobic cycles. During the anaerobic phase, propionate was converted to polyhydroxyalkanoates (PHA) with the following monomer composition: hydroxyvalerate, 74.2%; hydroxymethylvalerate, 16.9%; hydroxymethylbutyrate, 8.6%; and hydroxybutyrate, 0.3%. The isotopic enrichment in the different carbon atoms of hydroxyvalerate (HV) produced during the first anaerobic stage was determined: HV5, 59%; HV4, 5.0%; HV3, 1.1%; HV2, 3.5%; and HV1, 2.8%. A large proportion of the supplied label ended up on carbon C-5 of HV, directly derived from the pool of propionyl-coenzyme A (CoA), which is primarily labeled on C-3; useful information on the nature of operating metabolic pathways was provided by the extent of labeling on C-1, C-2, and C-4. The labeling pattern on C-1 and C-2 was explained by the conversion of proplonyl-CoA to acetyl-CoA via succinyl-CoA and the left branch of the tricarboxylic acid cycle, which involves scrambling of label between the inner carbons of succinate. This constitutes solid evidence for the operation of succinate dehydrogenase under anaerobic conditions. The labeling in HV4 is explained by backflux from succinate to propionyl-CoA. The involvement of glycogen in the metabolism of propionate was also demonstrated; moreover, it was shown that the acetyl moiety to the synthesis of PHA was derived preferentially from glycogen. According to the proposed metabolic scheme, the decarboxylation of pyruvate is coupled to the production of hydrogen, and the missing reducing equivalents should be derived from a source other than glycogen metabolism.